Phenotypical Diversification of Early IFNα-Producing Human Plasmacytoid Dendritic Cells Using Droplet-Based Microfluidics - Van Eyndhoven, Laura C.; Chouri, Eleni; Subedi, Nikita; Tel, Jurjen (Frontiers in Immunology, 2021)
Plasmacytoid dendritic cells (pDCs) are a rare type of highly versatile immune cells that besides their specialized function of massive type I interferon (IFN-I) production are able to exert cytotoxic effector functions. However, diversification upon activation leads to highly heterogeneous responses that have not been fully characterized yet. Using droplet-based microfluidics, we showed that upon toll like receptor (TLR)-induced single-cell activation only 1% secretes IFNα, and only small fractions upregulate cytotoxicity markers. Interestingly, this 1% of early IFN-producing pDCs, also known as first responders, express high levels of PD-L1 and TRAIL, which makes these hybrid cells similar to earlier described IFN-I producing killer pDCs (IKpDCs). IFN-I priming increases the numbers of IFNα producing cells up to 40%, but does not significantly upregulate the cytotoxicity markers. Besides, these so-called second responders do not show a cytotoxic phenotype as potent as observed for the first responders. Overall, our results indicate that the first responders are the key drivers orchestrating population wide IFN-I responses and possess high cytotoxic potential.